Management of giving warm compresses to the abdominal wall with pain problems - Maria Kurni Menga; Suprapto Suprapto; Nursyamsi Norma Lalla; A. Syamsinar Asmi; Lukman Waria; Fatimah Fatimah (Jurnal Edukasi Ilmiah Kesehatan, 2023)
Warm compress therapy on the abdominal wall has been known as a practical approach to overcoming pain problems. Through increasing local temperature, this therapy can relieve muscle tension, improve blood circulation, and provide pain relief. Qualitative research with a descriptive case study approach. The subjects of this case study used 2 clients with the same diagnosis, the same problem, and the same application of intervention. The results found that the pain felt in both patients, Mrs. R and Mrs. W experienced a significant decrease daily. On day I, Mrs. R, the pain experienced on a scale of 5 and decreased; on day 3, the pain was no longer felt. While Mrs. W on the day I, the pain experienced with skal 4. After compressing warm water on the dining abdomen, the pain felt every day was reduced and disappeared or did not feel pain on day 3 after the implementation. The conclusion of applying warm compress therapy is that this method gives patients greater control in managing their abdominal pain. With a deep understanding of the effectiveness of warm compress therapy, it can be a valuable element in a holistic pain management strategy.